2016
DOI: 10.1038/srep31929
|View full text |Cite
|
Sign up to set email alerts
|

Hypomineralized Second Primary Molars as Predictor of Molar Incisor Hypomineralization

Abstract: Molar incisor hypomineralization (MIH) is a developmental defect of dental enamel that shares features with hypomineralized second primary molars (HSPM). Prior to permanent tooth eruption, second primary molars could have predictive value for permanent molar and incisor hypomineralization. To assess this possible relationship, a cross-sectional study was conducted in a sample of 414 children aged 8 and 9 years from the INMA cohort in Valencia (Spain). A calibrated examiner (linear-weighted Kappa 0.83) performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
72
3
7

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 27 publications
5
72
3
7
Order By: Relevance
“…Studies conducted in different countries reported the prevalence of HSPM varying from 2.5% to 21.8% . In the present population‐based study, the prevalence was 14.9%, comparable to those found in and Australia (14.1%) and Spain (14.5%) .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Studies conducted in different countries reported the prevalence of HSPM varying from 2.5% to 21.8% . In the present population‐based study, the prevalence was 14.9%, comparable to those found in and Australia (14.1%) and Spain (14.5%) .…”
Section: Discussionsupporting
confidence: 81%
“…When the HSPM affects two or more teeth, there is a 7.82‐fold increase in the chances of developing molar‐incisor hypomineralization (MIH) . The amelogenesis of the permanent first molars and primary second molars present a coincident period, and injuries that occur during this moment can affect both dentitions . It is assumed that the change in the maturation process of the enamel varies according to the intensity of the aggressor agent so that the more intense the injury, the greater the number of primary second molars affected.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequently suggested factors are neonatal problems (prematurity and/or low birth weight), early childhood illnesses (asthma or bronchitis), fever, hospitalization, oxygenation without intubation, and antibiotic therapy. Some authors have suggested a genetic‐based etiology . The prevalence of MIH in children and adolescents varies among different studies, with reported values between 2.8% and 40% .…”
Section: Introductionmentioning
confidence: 99%